2008
DOI: 10.1128/mmbr.00018-08
|View full text |Cite
|
Sign up to set email alerts
|

How Phosphotransferase System-Related Protein Phosphorylation Regulates Carbohydrate Metabolism in Bacteria

Abstract: It is incorrect that growth of Escherichia coli on fructose and a less favorable carbon source leads to diauxic growth. In fact, J. Monod (Recherches sur la Croissance des Cultures Bactériennes, 1942) reports that he observed biphasic growth of E. coli cells with glucose or mannitol as the "preferred" carbon source but not with fructose. Page 954, column 2: The first paragraph of the "Diauxic Growth" section refers specifically to the diauxic growth of Bacillus subtilis, the first organism for which diauxie wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
788
2
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(808 citation statements)
references
References 0 publications
7
788
2
11
Order By: Relevance
“…More than one hundred years ago, people found that the presence of the preferred sugar glucose represses the synthesis of some enzymes, which is necessary for the metabolism of less favourable carbon sources, such as glycosides. This phenomenon became known as carbon catabolite repression (Deutscher et al 2006). However, in the present study glucose showed an enhanced effect on the βG activity of SD-2a and 31MBR intact cells.…”
Section: Resultscontrasting
confidence: 45%
“…More than one hundred years ago, people found that the presence of the preferred sugar glucose represses the synthesis of some enzymes, which is necessary for the metabolism of less favourable carbon sources, such as glycosides. This phenomenon became known as carbon catabolite repression (Deutscher et al 2006). However, in the present study glucose showed an enhanced effect on the βG activity of SD-2a and 31MBR intact cells.…”
Section: Resultscontrasting
confidence: 45%
“…It has been known for quite some time that the activity of BglG homologs depends on the general PTS proteins. In Grampositive bacteria, activation of BglG-like factors involves their phosphorylation by HPr, 7 but in E. coli this activation is phosphorylation-independent. 18 Indeed, we have now shown that the interaction of BglG with the different PTS components, which determines its subcellular localization, does not depend on the phosphorylation state of the different players.…”
Section: Spatial Organization Of Bacterial Signaling Systemsmentioning
confidence: 99%
“…The PTS enables hierarchal uptake of carbon sources and appropriate adjustment of cell metabolism via the control of global regulatory systems, such as catabolite repression and inducer exclusion. 7 The chemotaxis system enables navigation of bacterial cells along gradients, with carbon source gradients having a major impact. 8,9 Together, these systems can be regarded as a microbrain or as the bacterial metabolic nervous system.…”
Section: Spatial Organization Of Bacterial Signaling Systemsmentioning
confidence: 99%
“…It serves as an enzyme-coupled transport system that modifies its substrate sugars by phosphorylation concomitant with transport (Meadow et al, 1990). It also mediates catabolite repression, regulates cytoplasmic inducer levels and coordinates nitrogen metabolism with carbon metabolism (Deutscher et al, 2006;Pflüger-Grau & Görke, 2010;Saier, 1989;Saier et al, 1996). This system uses an elaborate signal transduction pathway and can sense and respond to external stimuli as well as the internal metabolic status of the cell.…”
Section: The Bacterial Phosphotransferase System (Pts)mentioning
confidence: 99%